Self-Balancing Sanctuarying - Ruth Tiffany Naylor (Grounded Theory Review: An International Journal)
This author aimed to set out a grounded theory (GT) of relaxation as it is carried out under the normal pressures and tensions of everyday life. After switching from using the Corbin and Strauss grounded theory (2008) design to classic grounded theory, the author discovered a five-step theoretical causal-consequence model emerged from the analysis of what 21 non-anxious-to-slightly-anxious people from the community said what they do to relax. Their main concern is self-balancing. A disturbed sense of ease (cause) arising from internal and external threats (context) leads to resolution by switching (core category) in safety (condition). The chosen switching activities are self- emergent. Their continuing use depends upon transforming hindrances and integrating feedback to the process to maximize benefits (contingencies and consequences). Three switching strategies are central. Benefits not consciously or analytically generated are restoring, refreshing, and re-energizing me; maintaining and building me; and growing and developing me. Restoring, refreshing, and re-energising me is characterized by a sense of well-being and lifted mood; maintaining and building me is characterized by integrating and strengthening the core self and connecting to the community; growing and developing me is characterized by expanding self-discovery. Theoretically situating extant descriptive and conceptual models of relaxation is one of the many contributions this research makes.